Prevalence and Nature of Spiritual Distress Among Palliative Care Patients in India - Gielen, Joris (Journal of religion and health, 2017)
In palliative care research, little attention has been paid to the empirical study of spirituality in patients in non-Western countries. This study describes the prevalence and nature of spiritual distress among Indian palliative care patients. Data from 300 adult cancer patients who had completed a questionnaire with 36 spirituality items were analyzed. Spirituality was shaped by the Indian religious and economic context. A latent class analysis resulted in three clusters: trustful patients (46.4 %), spiritually distressed patients (17.4 %), and patients clinging to divine support (36.2 %). After regression, the clusters were found to be associated with pain scores (p < .001), gender (p = .034), and educational level (p < .006). More than half of the patients would benefit from spiritual counselling. More research and education on spirituality in Indian palliative care is urgently required.